2006
DOI: 10.4049/jimmunol.176.7.4315
|View full text |Cite
|
Sign up to set email alerts
|

Complement Component C3 Is Required for Protective Innate and Adaptive Immunity to Larval Strongyloides stercoralis in Mice

Abstract: This study examines the role of complement components C3 and C5 in innate and adaptive protective immunity to larval Strongyloides stercoralis in mice. Larval survival in naive C3−/− mice was increased as compared with survival in wild-type mice, whereas C3aR−/− and wild-type mice had equivalent levels of larval killing. Larval killing in naive mice was shown to be a coordinated effort between effector cells and C3. There was no difference between survival in wild-type and naive C5−/− mice, indicating that C5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 45 publications
(55 reference statements)
2
39
0
Order By: Relevance
“…In vitro studies have demonstrated that the serum components complement and fibronectin are required for eosinophil binding and degranulation resulting in the killing of N. brasiliensis larvae (58). Complement component C3 has been shown to be required for innate immunity to S. stercoralis (35). It has also been reported that the purified human eosinophil granule products major basic protein and eosinophil cationic protein are directly toxic to larval S. stercoralis in the absence of any other cells or factors (51).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated that the serum components complement and fibronectin are required for eosinophil binding and degranulation resulting in the killing of N. brasiliensis larvae (58). Complement component C3 has been shown to be required for innate immunity to S. stercoralis (35). It has also been reported that the purified human eosinophil granule products major basic protein and eosinophil cationic protein are directly toxic to larval S. stercoralis in the absence of any other cells or factors (51).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a surface FcR might bind Ig in an unfavorable orientation and thereby limit its ability to activate complement. In mice infested with larval Strongyloides stercoralis, C3 was not required for the development of adaptive immunity, but was necessary for the larval killing process during both protective innate and adaptive immune responses (13).…”
mentioning
confidence: 99%
“…In mice, several components of protective primary and secondary immunity to the parasite have been described (17). Molecules from larval S. stercoralis directly recruit granulocytes to the parasite microenvironment (18)(19)(20), where they kill the parasite in collaboration with complement component C3 (21), eosinophil major basic protein, and neutrophil-derived myeloperoxidase (22,23). The cellular composition of the parasite microenvironment in naive mice consists of high numbers of neutrophils, eosinophils, and macrophages (22).…”
mentioning
confidence: 99%